Strategies For Managing Productive Waqf In Economic Empowerment: A Case Study Of Ihmal Market In Aceh Tengah - Syaripuddin Syaripuddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Waqf is considered one of the most fundamental instruments in Islamic economic studies, holding significant potential for empowering the economy. This study focuses on analyzing the management of productive waqf in relation to the economic empowerment of the Muslim community. The primary aim is to examine the management practices of productive waqf at Ihmal Market and assess its impact on the economic empowerment of the local Muslim population in Aceh Tengah Regency. The research employs a qualitative method and is conducted as a field study. The findings indicate that while the productive waqf at Ihmal Market is managed professionally, its impact has not yet resulted in a direct and substantial contribution to the economic empowerment of the community.